Chemical composition and antimicrobial activity of essential oils from selected herbs cultivated in the South of Brazil against food spoilage and foodborne pathogens - Silveira,Sheila Mello da (2012)
The chemical composition of 10 selected plant essential oils obtained by steam distillation was determined by GC and GC/MS. The antimicrobial activity of the essential oils was screened against 12 important food-related bacterial strains by agar disc-diffusion assay. MIC and MBC were determined for the essential oils that presented the highest activity in the agar disc-diffusion test. The most active essential oils against the tested bacteria were, in descending order, lemongrass (Cymbopogon flexuosus), basil (Ocimum basilicum), oregano (Origanum vulgare), cinnamon leaf (Cinnamomum zeylanicum), and laurel (Laurus nobilis). Except for S. Typhimurium, the tested bateria were inhibited at MIC values lower or equal to 0.62mg mL-1 by lemongrass (Cymbopogon flexuosus) essential oil. Yersinia enterocolitica presented the highest sensitivity to all essential oils tested (CMI≤0.62mg mL-1). There was a significant correlation (P<0.05) between oxygenated monoterpenes levels in the essential oils and MIC and MBC values against Escherichia coli. Results showed that the evaluated essential oils present high potential as natural preservatives.